2013
DOI: 10.1177/0733464812470747
|View full text |Cite
|
Sign up to set email alerts
|

Gaming for Health

Abstract: This systematic review examined the physical and cognitive effects of physically based interactive computer games (ICGs) in older adults. Literature searching was carried out from January 2000 to June 2011. Eligible studies were trials involving older adults (>65 years) describing the effects of ICGs with a physical component (aerobic, strength, balance, flexibility) on physical or cognitive outcomes. Secondary outcomes included adverse effects, compliance, and enjoyment. Twelve trials met the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(72 citation statements)
references
References 32 publications
(98 reference statements)
2
68
0
2
Order By: Relevance
“…They found that cognitive function was improved among the cybercyclers, and that it was likely that it would help to prevent cognitive decline compared to traditional exercise. Overall, while there has been significant work in this area, a systematic review carried out by Bleakley et al (2013) found that although these types of approach are safe and effective, that that there is limited high quality evidence currently available.…”
Section: Exercisementioning
confidence: 99%
“…They found that cognitive function was improved among the cybercyclers, and that it was likely that it would help to prevent cognitive decline compared to traditional exercise. Overall, while there has been significant work in this area, a systematic review carried out by Bleakley et al (2013) found that although these types of approach are safe and effective, that that there is limited high quality evidence currently available.…”
Section: Exercisementioning
confidence: 99%
“…Recent research has gradually integrated this technique as a valuable therapeutic tool in the rehabilitation of older people [8][9][10][11][12][13][14][15]. Indeed, VR, especially in the form of serious games (SGs), combines therapeutic and recreational challenges [16]. This implicit interactive strategy prevents boredom, making the therapy less tiring and dispiriting.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies using VR are based on commercially available games designed for the entertainment of healthy people [16]. Studies have shown different VR systems with specific interfaces, graphics, sceneries, principles of gameplay, and presentation of scores.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews on intervention studies of exergaming have already been published. [15][16][17][18][19][20] However, the systematic reviews have focused on children, 15 on those in a very broad age group, [16][17][18][19] or on both healthy and diseased elderly participants. 20 Several overview articles have recently been published reviewing the current status of exergaming on specifically elderly adults.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20] However, the systematic reviews have focused on children, 15 on those in a very broad age group, [16][17][18][19] or on both healthy and diseased elderly participants. 20 Several overview articles have recently been published reviewing the current status of exergaming on specifically elderly adults. [21][22][23][24] However, these articles have had an explorative approach (e.g., they have not conducted a systematic literature search, and they have included different study designs).…”
mentioning
confidence: 99%